2015
DOI: 10.1186/s13287-015-0001-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of whole bone marrow, whole bone marrow cultured cells, and mesenchymal stem cells in chronic wound healing

Abstract: IntroductionRecent evidence has shown that bone marrow cells play critical roles during the inflammatory, proliferative and remodeling phases of cutaneous wound healing. Among the bone marrow cells delivered to wounds are stem cells, which can differentiate into multiple tissue-forming cell lineages to effect, healing. Gaining insight into which lineages are most important in accelerating wound healing would be quite valuable in designing therapeutic approaches for difficult to heal wounds.MethodsIn this repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 26 publications
1
53
0
1
Order By: Relevance
“…However, these methods provide very limited results in most cases (up to 50%) and new therapies are required to overcome the current challenges of chronic wound management (Greer et al, 2013; Dreifke et al, 2015; Rowan et al, 2015; Sessions et al, 2017). Recent studies have indicated that cell based therapies can provide a suitable alternative treatment method for multiple pathological conditions including, wound healing (Chen et al, 2012; Rodriguez-Menocal et al, 2015; Duscher et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…However, these methods provide very limited results in most cases (up to 50%) and new therapies are required to overcome the current challenges of chronic wound management (Greer et al, 2013; Dreifke et al, 2015; Rowan et al, 2015; Sessions et al, 2017). Recent studies have indicated that cell based therapies can provide a suitable alternative treatment method for multiple pathological conditions including, wound healing (Chen et al, 2012; Rodriguez-Menocal et al, 2015; Duscher et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The dysfunctional healing of the wounds in this study can be characterized by inhibition of the inflammatory response, dysfunctional macrophages leading to an inability to combat infection, impaired angiogenesis and vasculogenesis, accumulation of fibrous tissue, and aberrant extracellular matrix accumulation. 13 There is no consensus definition of a chronic wound, but most consider a wound to be chronic if it has not healed in 4-6 weeks. 14 The recorded number of NPWT treatments patients received before dressing collection for this study ranged from 1 (one patient) to 14 (one patient).…”
Section: Resultsmentioning
confidence: 99%
“…RodriguezMenocal et al (35) demonstrated decreased motility and migration capability of MSCs in an irradiated murine delayed wound healing model. Henke et al (36) reported decreased motility and contractility in prostate CAFs, in their study associated with an increase of focal adhesion kinase.…”
Section: Discussionmentioning
confidence: 99%